The role of architecture on urban revitalisation: the Case of Olympic Arenas in Berlin - Prenzlauer Berg - Gabriel M. Ahlfeldt; Wolfgang Maennig (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2007)
This paper investigates socioeconomic impacts of three multifunctional sports arenas situated in Berlin-Prenzlauer Berg, Germany. The three arenas were chosen for their potential to contribute to revitalisation of their economically deprived neighbourhoods. We employ a difference-in-differences approach to check for structural breaks in development of land values within areas of potential impact. Our results suggest that arenas emanate positive externalities and apparently have accelerated the process of gentrification going on in Prenzlauer Berg. However, evidence also supports concerns that congestion problems may adversely affect property values, at least when not addressed appropriately during planning.
Keywords: R53; R58; 330; Stadium Impact; Stadium Architecture; Gentrification; Berlin